Long‐term use of dienogest for the treatment of primary and secondary dysmenorrhea. Issue 4 (12th February 2020) - Osuga, Yutaka; Hayashi, Koichi; Kanda, Shingo
Abstract: Aim: To investigate the safety and efficacy of dienogest (DNG), a progestational 19‐norsteroid, administered for 52 weeks in patients with primary and secondary dysmenorrhea. Methods: A total of 147 patients with dysmenorrhea received 1 mg of DNG orally each day for 52 weeks. The dose could be increased to 2 mg/day at or after Week 12 according to the investigator's determination. The primary safety endpoint was evaluation of adverse events, and the secondary safety endpoint was evaluation of adverse drug reactions. The number of days and severity of genital bleeding were assessed according to records in the patients' diary. Lower abdominal pain and/or low back pain because of dysmenorrhea were assessed according to the dysmenorrhea score. Results: The most frequent adverse drug reaction was irregular uterine bleeding (94.6%). Most subjects completed the 52‐week administration. Genital bleeding was more likely to occur in subjects with secondary dysmenorrhea than in those with primary dysmenorrhea, and in subjects with "uterine myoma or adenomyosis" than in those with "endometriosis alone." In any of the categorizations, there tended to be fewer days with genital bleeding as the treatment period increased in length, and most of the genital bleeding cases were mild. The change from baseline in the dysmenorrhea score (mean ± standard deviation [SD]) was −3.7 ± 1.6 at Week 24 of treatment and −4.0 ± 1.3 at Week 52. Conclusion: This study showed favorable tolerability of the long‐term use of DNG to patients with dysmenorrhea and a sustainable pain relief effect.